PNEUMATIC WEAPONS AND THEIR TECHNICAL PROPERTIES - Turakhanov Akrom Abdullahakimovich; Koraboev Sarvarbek (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides a brief overview of pneumatic weapons and their technical features. This article is intended to acquaint students (students) of higher, secondary special and secondary educational institutions with information about pneumatic weapons and their technical characteristics.